Impact of eosinophil‐peroxidase (EPX) deficiency on eosinophil structure and function in mouse airways. Issue 1 (4th October 2018) - Percopo, Caroline M.; Krumholz, Julia O.; Fischer, Elizabeth R.; Kraemer, Laura S.; Ma, Michelle; Laky, Karen; Rosenberg, Helene F.
Abstract: Eosinophil peroxidase (EPX) is a major constituent of the large cytoplasmic granules of both human and mouse eosinophilic leukocytes. Human EPX deficiency is a rare, autosomal‐recessive disorder limited to the eosinophil lineage. Our intent was to explore the impact of EPX gene deletion on eosinophil content, structure, and function. In response to repetitive intranasal challenge with a filtrate of the allergen, Alternaria alternata, we found significantly fewer eosinophils peripherally and in the respiratory tracts of EPX −/− mice compared to wild‐type controls; furthermore, both the major population (Gr1 −/lo ) and the smaller population of Gr1 hi eosinophils from EPX −/− mice displayed lower median fluorescence intensities (MFIs) for Siglec F. Quantitative evaluation of transmission electron micrographs of lung eosinophils confirmed the relative reduction in granule outer matrix volume in cells from the EPX −/− mice, a finding analogous to that observed in human EPX deficiency. Despite the reduced size of the granule matrix, the cytokine content of eosinophils isolated from allergen‐challenged EPX −/ − and wild‐type mice were largely comparable to one another, although the EPX −/− eosinophils contained reduced concentrations of IL‐3. Other distinguishing features of lung eosinophils from allergen‐challenged EPX −/− mice included a reduced fraction of surface TLR4 + cells and reduced MFI for NOD1. Interestingly, the EPX gene deletion had no impact on eosinophil‐mediated clearance of gram‐negative Haemophilus influenzae from the airways. As such, although no clinical findings have been associated with human EPX deficiency, our findings suggest that further evaluation for alterations in eosinophil structure and function may be warranted. Abstract : Eosinophils from the lungs of allergen‐challenged EPX −/− mice display differential expression of Siglec F and maintain reduced quantities of IL‐3.